Pengetahuan Lansia Tentang Penggunaan Gigi Palsu Di Panti Werdha Hargo Dedali Surabaya - Alya Rahma; Sunomo Hadi; Agus Marjianto (Poltekkes Kemenkes Surabaya, 2024)
Introduction : Elderly (elderly) is someone aged 60 years and over who has a different appearance compared to other age groups. Older people often neglect oral hygiene and often complain of toothaches such as loose teeth, tooth decay, swollen gums and receding gums. Loss of all or part of the teeth has the same impact on the inability to survive. Dentures are basically designed to improve the function of chewing, speaking, esthetics, maintaining tissue health and preventing further structural damage to organs in the oral cavity. Problem : the problem in this study is the use of dentures at the Hargo Dedali nursing home is included in the less category. The Purpose : The purpose of this study was to determine the knowledge of the elderly about the use of dentures at the Hargo Dedali Nursing Home in Surabaya. Metods : This research is descriptive in nature and was carried out in March 2023 with 25 elderly respondents using a questionnaire. data analysis technique by calculating the results of the data that has been collected and presented in tabular form. Result : Based on the results of the study, it was found that the knowledge of the elderly about the definition of dentures was in the sufficient category, the knowledge of the elderly about the function of using dentures was in the sufficient category, the knowledge of the elderly about how to care for dentures was in the less category, the knowledge of the elderly about the consequences of not using dentures was in the less category. Conclusion : The knowledge of the elderly regarding the use of dentures at the Hargo Dedali nursing home in Surabaya was found to be lacking.